Local-Wisdom-Based Character Education Management in Early Childhood Education - Ernawati, Turini; Siswoyo, Rasdi Eko; Hardyanto, Wahyu; Raharjo, Tri Joko (The Journal of Educational Development, 2018)
Efforts to prepare better future generations through local character education based on local wisdom should be done since early childhood. The purpose of this research is to explain (1) the implementation of character education based on local wisdom, (2) character education management based on local wisdom, and (3) factors that influence the management of character education based on local wisdom. Data were drawn using (1) interviews, (2) participant observation, and (3) documentation techniques. The data were analyzed by means of an interactive model consisting of data collection, data reduction, data display, and inference. The results show that (1) the character values taught in PAUD KB Al-Irsyad Al-Islamiyah Cirebon City adopt the kinship system which is one of the local cultural centers in Cirebon City. The local wisdom of the communities in Cirebon is derived from SGJ, especially the sayings of SGJ which imply piety, belief, discipline, wisdom, policy, decency, manners and social life; (2) the character education management that is based on the local wisdom includes planning, implementation, and supervision; (3) the supporting factors in the implementaton of the character education management include the government support, human resources, facilities, programmed activities, support of school residents, parents, and surrounding communities. The inhibiting factors include limited control of the school after the students are off school and the influence of the media. The local wisdom based character education is planned with reference to the school vision, i.e. "Forming a smart, good, skilled, and noble learnerâ€. Character education can be integrated into every subject and linked to the context of everyday life. As a supervisor, the principal has supervised and guided the teacher periodically during each turn of the school year. The learning method that is based on local wisdom is in accordance with the reference of the Directorate of Early Childhood Education. The results of this study can be used as a reference for preparing and planning the management of local-based character education in early childhood education, and providing input for PAUD managers in developing and implementing the model of planning, implementation, and supervision of character education that is based on local wisdom.